Research on SOFC Properties of Low Concentration Gas Fuel and SFM-GDC Reforming - Han Chao; Dong Xinyue; He Leiyi; Xu Jin; Li Pengxiang; Li Jiakang (E3S Web of Conferences, 2023)
When gas fuel is used in solid oxide fuel cells, methane cracking occurs at high temperature in the Ni-based anode, forming granular carbon deposition in the active site of the anode, and finally completely wrapped Ni metal, greatly losing the electrochemical performance. Therefore, it is very necessary to add a reforming catalytic layer in the anode of the battery. The methane is reformed into CO and H2 fuel before entering the anode, and the place where methane cracking occurs is mostly transferred to the reforming layer, which reduces the catalytic reforming burden of the Ni-based anode, so as to effectively improve the battery performance. In this paper, Sr2Fe1.5Mo0.5O6 with double perovskite structure was synthesized and prepared, which maintained very good stability in high temperature REDOX atmosphere and had high electrical conductivity. The combination of GDC and SFM can increase the reaction site of the three-phase interface of the reforming layer, and also help to improve the thermal expansion matching between the reforming layer and anode. In this paper, the electrochemical performance of straight cell coated with SSFM-GDC reforming layer has been studied. Low concentration gas in coal mine contains methane, oxygen, nitrogen, and water hydrogen sulfide, etc., and its reaction process in solid oxide fuel cells is complicated. Therefore, studying the reaction mechanism of low concentration gas in solid oxide fuel cells has important practical significance for promoting its application.